PENERAPAN IPTEKS KEABSAHAN PENDAFTARAN TANAH DI KAMPUNG ASEI KECIL, JAYAPURA - Kadir Katjong; James Yoseph Palenewen; Silvester Magnus L. Palit (LPPM Uncen, 2021)
This service was carried out under the title Implementation of Land Registration Legality Science and Technology, which was carried out in the village of Asei Kecil Sentani Timur, Jayapura Regency, activities carried out to partners were due to cases from partners regarding the lack of understanding of the importance of land registration so that with the expertise possessed by the servants they could implement the IPTEKS. The method of implementing this service is carried out by applying science and technology through lectures and discussions held on Saturday, August 15, 2020 which was held at the village hall as well as assistance to partners carried out to date, this activity begins with preparation and coordination, then the presentation of material rights- land rights and land registration, namely assistance in the preparation of the required documents for land registration. The output of this service is the increased knowledge of partners regarding land rights and guaranteed tenure with land registration, completeness of land registration as pre-adjudication with the aim of making it easier for partners to complete land registration.Keywords: Land Registration, legality document, Sentani, Asei Kecil, Jayapura